Making Health Reform Work: The View from the States - DiIulio, John J.; Nathan, Richard P. (Rowman & Littlefield Publishers, 2010)
Nearly everyone agrees that the nation's health care system needs to be reformed. By mid-1994 over a half-dozen major reform plans were under consideration in Congress. But beyond the political challenge of passing a reform package lies an even bigger challengehow to make health reform work! Critics of the Clinton plan have charged that it's too complex and doomed to administrative failure. Are they right? The nation's health care finance and delivery systems are already immensely complex and problem-ridden. Is it possible to achieve meaningful reforms without adopting new administrative strategies and structures that are equally complex? What role do the states now play in administering the nation's health care system? Is it possible to design administrative success into national health reform plans from the start? Produced in close consultation with state health care officials from all around the country, this important volume offers practical and timely recommendations for how to make health reform work. It addresses the central implementation, management, and federalism dimensions of reform. Chapters by some of the country's leading health policy and public management experts explore the administrative challenges of reform as they relate to health alliances, cost containment, quality of care, medical education and training, and other key issues. They discuss various working principles for developing an administratively sound health reform policy. The contributors are Lawrence D. Brown and Michael Sparer, Columbia University; Gerald Garvey, Princeton University; Donald F. Kettl, University of Wisconsin-Madison; James R. Tallon, United Hospital Fund; James W. Fossett and Frank J. Thompson, State University of New York, Albany.